Hair loss after SARS-CoV2 Infection - Beata Kuczyńska; Magdalena Czelej; Konrad Gładysz; Krzysztof Gieroba; Marcin Szydłowski; Aleksander Kłos; Justyna Szydłowska; Olga Żuchnik; Olgierd Król; Piotr Kwiatkowski (Kazimierz Wielki University, 2022)
Introduction:Since the detection of SARS-CoV-2 in China, more than 3.8 million people have died. A big problem is the long-term effects and complications of this disease. The pathogenesis of these long-term effects is not fully known. Significant increases in pro-inflammatory cytokines have been observed among people with complications. Their dermatological manifestations are due to the presence of receptors for angiotensin-converting enzyme 2 in the skin and other tissues. Aim of the study: Summary of current knowledge on the pathogenesis, diagnosis, treatment of hair loss after Covid-19. Methods and materials: A review of the literature available in the PubMed database, using the following terms: "Hair loss after Covid", "Tellgoen Effluvium covid", "Alopecia areata covid", "androgenetic alopecia covid". Results: The most commonly reported among the dermatological manifestations is hair loss, the predominant type of which is telogen alopecia, which involves a prolongation of the resting phase of the hair most likely due to an increase in pro-inflammatory cytokines and depletion of anticoagulant proteins, leading to microthrombosis. There has also been a significant increase in the incidence of alopecia areata, in the development of which, in addition to autoimmunity, psychological and physiological stress factors are also highly influential and are higher during the course of the disease including SARS-CoV2. Androgenetic alopecia results from excess androgens and increased sensitivity of hair follicles to them, transmembrane serine protease 2 facilitates the "entry" of the virus into the body by facilitating the binding of viral particles to ACE-2 receptors, which acts as a gateway.  Conclusion: Hair loss is not life-threatening however it has serious psychological and social implications, so it is very important to educate patients about the mechanism and treatment of this phenomenon.